Isotope Analysis (13C, 18O) of Wine From Central and Eastern Europe and Argentina, 2008 and 2009 Vintages: Differentiation of Origin, Environmental Indications, and Variations Within Countries - Horacek, Micha; Ogrinc, Nives; Magdas, Dana Alina; Wunderlin, Daniel; Sucur, Sanja; Maras, Vesna; Misurovic, Ana; Eder, Reinhard; Čuš, Franc; Wyhlidal, Stefan; Papesch, Wolfgang (Frontiers in Sustainable Food Systems, 2021)
In this study we compare the stable isotope composition of oxygen and carbon of wines from four Central and Southeastern European countries and from Argentina, to study the similarities and differences in the isotope signatures and thus the potential of differentiation of the various wine-growing countries. We observe similar trends for wine from Austria, Slovenia and Romania with respect to the vintages 2008 and 2009, which are absent in the Montenegrin and Argentinean samples. It is speculated that the weather develops similarly for Austria, Slovenia and Romania, as these countries are positioned at similar latitude and not too far away from each other (general central and eastern European weather situation), whereas Montenegro is not influenced by the latter being situated farther south and dominantly influenced by the Adriatic Sea. Investigations on further vintages are needed to test this assumption.